Visfatin expression in subcutaneous adipose tissue of pre-menopausal women: relation to hormones and weight reduction - Kováčiková, Michaela; Šiklová, Michaela; Klimčáková, Eva; Polák, Jan; Hejnová, Jindra; Bajzová, Magda; Kováčová, Zuzana; Viguerie, N; Langin, Dominique; Štich, Vladimír (European journal of clinical investigation, 2008)
Background: A novel adipokine, visfatin, was found to be related to adiposity in humans and regulated by a number of hormonal signals. The aim of this study was to investigate the relationships of visfatin expression in adipose tissue with potential regulatory factors such as insulin, testosterone and tumor necrosis factor-alpha (TNF-alpha) and to elucidate the effect of a diet induced weight reduction on adipose tissue mRNA expression and plasma levels of visfatin. MATERIALS AND METHODS: Biopsies of subcutaneous abdominal adipose tissue (SCAAT) and plasma samples were obtained at the beginning of the study from 47 pre-menopausal women (age 38.7 +/- 1.7 years, body mass index (BMI) 27.9 +/- 1.4 kg m(-2)), consisting of 15 lean, 16 overweight and 16 obese subjects. The subgroup of 32 overweight/obese women (age 42.1 +/- 1.9 years, BMI 31.2 +/- 0.9 kg m(-2)) underwent a 12 week hypocaloric weight reducing diet and samples were obtained at the end of the diet. Biopsy samples were analysed for visfatin and TNF-alpha mRNA levels and plasma was analysed for relevant metabolites and hormones. RESULTS: In the group of 47 subjects visfatin mRNA expression in SCAAT was negatively correlated with plasma free testosterone (r = -0. 363, P < 0.05) and BMI (r = -0.558, P < 0.01) and positively associated with adipose tissue TNF-alpha mRNA expression (r = 0.688, P < 0.01). The diet resulted in the reduction of body weight and in the decrease of plasma insulin, free testosterone and TNF-alpha levels. In the group of overweight/obese subjects visfatin mRNA in SCAAT increased after the diet and the diet induced increase was positively correlated with the magnitude of body weight loss. CONCLUSION: Visfatin mRNA expression in SCAAT is associated with TNF-alpha expression, plasma free testosterone and BMI in pre-menopausal women. A weight reducing hypocaloric diet results in the increase of visfatin mRNA in SCAAT.
Keywords: dospělí; hmotnostní úbytek; Hormones; index tělesné hmotnosti; nikotinamidfosforibosyltransferasa; Humans; lidé středního věku; Middle Aged; Nicotinamide Phosphoribosyltransferase; distribuce tělesného tuku; Financing, Organized; Body Mass Index; financování organizované; Subcutaneous Fat; Adult; Weight Loss; Statistics as Topic; podkožní tuk; hormony; ženské pohlaví; statistika jako téma; Body Fat Distribution; lidé; Female